Rethinking Sovereignty, Rethinking Revolution. - SMITH, MATTHEW NOAH (Philosophy & Public Affairs, 2008)
An essay on political revolution and political sovereignty is presented. The author discusses the legal right to revolution, the philosophy of sovereignty, and the paradigm of authorial systems. He unpacks consequentialist and Kantian objections to revolution and explores the moral aspects of revolution via governed communities. A philosophy and model of simultaneous sovereigns and global sovereignty are presented and are rooted in decentralization.